PERANCANGAN DAN PENGEMBANGAN APLIKASI WEB SEBAGAI PENUNJANG LAPORAN PADA LABORATORIUM IKEST MUHAMMADIYAH PALEMBANG - Paray Theo Lonando; Arif Fadillah (IKesT Muhammadiyah Palembang, 2023)
Background: Application is a subclass of computer software that directly utilizes computer capabilities to perform a task that the user wants. system for borrowing goods to manage reports and improve data on borrowing tools and labs that are not optimal online which can be accessed via desktops, smartphones or tablets so that they can facilitate the borrowing process. Research: This study uses data collection techniques using qualitative methods. Namely by interviews and observations as well as with the waterfall design. Result: The results of the research are making the development of the Muhammadiyah Palembang IKesT Lab lending application Conclusion: The conclusion of this research is the Development of an Application for Adding Features for lending special tools and labs for research and Adding Features for the Muhammadiyah Palembang IkesT Lab Report for researchers and students to the Muhammadiyah Palembang IkesT lab